Determinant of Customers’ Intention to Use Islamic Banking (Case Study in Jayapura City) - Pratiwi, Ira Eka; Affandy, Fachrudin Fiqri; Karman, Abdul (IKONOMIKA, 2020)
This study investigates the influence of faith, social influence, regulation, and bank functions on the intention to use Islamic banking. The study used quantitative method and the data was collected using a structured questionnaire. The sample consisted of 200 customers of one of the largest Islamic bank in Indonesia: Bank Mandiri Syariah, which is located in Jayapura, the capital city of Papua Province. The data were obtained by random sampling using through a face-to-face survey. The internal consistency reliability and validity test indicated that all scale items were proven reliable and valid. The multiple regression linear was used to analyze the influence of independent variables toward dependent variables. This study suggested that faith significantly affected the customers intention to use Islamic banking. Meanwhile, social influence, regulation, and bank functions did not show a significant influence on customers’ intention to use Islamic banking.Key words : Islamic Banking; Faith; Social Influence; Regulation; Bank Function